2020
DOI: 10.1101/2020.03.30.20047415
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for severe corona virus disease 2019 (COVID-19) patients : a systematic review and meta analysis

Abstract: medRxiv preprint Key PointsQuestion What are the risk factors for severe patients with corona virus disease 2019 ?Findings First in this review and meta-analysis, we found that elderly male patients with a high body mass index, high breathing rate and a combination of underlying diseases were more likely to develop into critically ill patients. second, compared with ordinary patients, severe patients had more significant symptom such as fever and dyspnea. Last, we also found that the laboratory test results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(60 citation statements)
references
References 36 publications
5
53
2
Order By: Relevance
“…Among those, we have found fatigue or myalgia, hypertension, and diabetes are significant risk factors that might lead to a critical state of COVID-19 patients. Some previous studies 8,12,13 also reported both diabetes and . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…Among those, we have found fatigue or myalgia, hypertension, and diabetes are significant risk factors that might lead to a critical state of COVID-19 patients. Some previous studies 8,12,13 also reported both diabetes and . CC-BY-NC-ND 4.0 International license It is made available under a is the author/funder, who has granted medRxiv a license to display the preprint in perpetuity.…”
Section: Discussionmentioning
confidence: 78%
“…From the random-effect meta-analysis, we conclude fever, cough, and diarrhea are insignificant risk factors for the severity of COVID-19. But a previous meta-analysis 8 published fever as a significant risk factor for the severity of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many conditions highlighted by our analysis have been previously reported [5,6,8] and are part of commonly used at-risk definitions [1,3], including hypertension, obesity, kidney and cardiovascular diseases. We do, however, identify a few additional risk factors, notably depression in patients 18-50 years old and males 65 years or more; and cognitive and neurological disorders in patients 65 years or older.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, these algorithms have been derived from a quickly growing number of epidemiological characterization studies (e.g., [5,6]), which report the prevalence of various conditions in a population of interest, typically severe COVID-19 patients. These studies provide timely and important information; however, identifying risk factors calls for a comparative analysis, contrasting the prevalence of conditions in case and control populations.…”
Section: Introductionmentioning
confidence: 99%